Economic Crisis in Argentina and no way out? - B. Fischer; U. Hiemenz; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
Argentina has made the headlines of international media not only for its successful return to democratic political rules in December 1983 but also for its renewed slump into economic crisis. The country is no longer able to meet the debt servicing requirements and to repay loans due this year while auspices for rescheduling and extending foreign debt are bleak. As a corollary tovexternal problems, there are high public sector deficits, inflation is accelerating at a galopping pace, and net private investment has turned negative. Up to now, the new democratic government has not lived up to expectations since it did not present a reform package designed to overcome the severe economic problems of the country. Rather, the government has relied on some ad-hoc emergency measures in an attempt to prevent the crisis from turning into catastrophy.
Keywords: 330